Bees algorithm technique for solving economic dispatch / Shahrizan Jabar - Jabar, Shahrizan (2012)
This paper presents an application of Bee Algorithm (BA) for solving Economic Dispatch (ED) problem in 6-units and 15-units system. In order to run the BA operation, there are several factors that under consideration such as complete ED problem formulation prohibited operating zones and cost fuel. BA is applied to solve Economic Dispatch (ED) problem to show the efficiency by comparing to those achieved from conventional approaches such as simulated annealing (SA) and Particle Swarm Optimization (PSO). As expected, BA operation more efficiency in terms of lowest fuel cost of generation and faster computational time rather than the conventional approaches.